2000
DOI: 10.1002/(sici)1099-1050(200004)9:3<199::aid-hec514>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of capitation on GPs' referral decisions

Abstract: In the Norwegian capitation trial, the payment system for general practitioners (GPs) has been changed; a practice allowance component has been replaced by a capitation component and the fee-per-item component constitutes a smaller part of a GPs practice income than previously. From the theoretical modelling of GPs' referral decisions, we predict that the replacement of the practice allowance by a capitation component will increase the rate of referrals to specialists. This hypothesis is supported by an explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 6 publications
2
37
0
Order By: Relevance
“…For four Norwegians municipalities, a 1993 trial replaced a GP's practice allowance by a capitation based on the practice size. Iversen and Lurås (2000) predict that this payment change would lead to a higher referral rate due to GPs shifting treatment costs to specialists. Norwegian data for one municipality before and after the introduction of capitation support the predictions.…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…For four Norwegians municipalities, a 1993 trial replaced a GP's practice allowance by a capitation based on the practice size. Iversen and Lurås (2000) predict that this payment change would lead to a higher referral rate due to GPs shifting treatment costs to specialists. Norwegian data for one municipality before and after the introduction of capitation support the predictions.…”
Section: Introductionsupporting
confidence: 55%
“…Iversen and Lurås (2000) model a GP who decides on the number of patients in his practice and referrals of patients to specialists. For four Norwegians municipalities, a 1993 trial replaced a GP's practice allowance by a capitation based on the practice size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…System change interventions included the community provision of specialist services by GPs (n = 9), [108][109][110][111][112][113][114][115][116][117] outreach or community provision by specialists (wholescale provision of a hospital service within the community) (n = 10), [118][119][120][121][122][123][124][125][126][127] return of inappropriate referrals (n = 2), 128,129 the provision of additional primary care staff (n = 3), [130][131][132] the addition or removal of gatekeeping systems (requiring a primary care provider to give access to secondary care services) (n = 4), [133][134][135][136] changes to payment systems (n = 4), [137][138][139] and referral management centre or other major triage systems (n = 6). [140][141][142][143][144][145][146] The overall picture for interventions that aim to implement large system changes to impact on referral is mixed. Two of the types of interventions for which stronger evidence was identified involved the provision of specialist services in the community: either outreach/community provision by specialists or community provision of specialist services by specially trained GPs (positive effects on referral rate, appropriate referrals, patient satisfaction, and service accessibility).…”
Section: Box 1 Main Search Strategymentioning
confidence: 99%
“…For example, Krasnik et al (1990) conducted a panel study in Denmark and found that general practitioners respond to a replacement of pure lumpͲsum payments by CAP supplemented by a FFS component by raising diagnostic and curative services and decreasing referrals to secondary care. Concerning referral rates, Iversen and Lurås (2000) obtain a similar result for Norway. They observe that referrals from primary to secondary care revealed by Norwegian general practitioners are larger under a CAPͲscheme with a reduced FFSͲcomponent than under a scheme with a fixed payment (practice allowance component) complemented by a FFSͲ payment.…”
Section: Introductionmentioning
confidence: 99%